MoSi2 Oxidation in 670–1498 K Water Vapor. Issue 4 (8th March 2016) - Sooby Wood, Elizabeth; Parker, Stephen S.; Nelson, Andrew T.; Maloy, Stuart A.
Abstract : Molybdenum disilicide (MoSi2 ) has well documented oxidation resistance at high temperature (T > 1273 K) in dry O2 containing atmospheres due to the formation of a passive SiO2 surface layer. However, its behavior under atmospheres where water vapor is the dominant species has received far less attention. Oxidation testing of MoSi2 was performed at temperatures ranging from 670–1498 K in both 75% water vapor and synthetic air (Ar‐O2, 80%–20%) containing atmospheres. Here the thermogravimetric and microscopy data describing these phenomena are presented. Over the temperature range investigated, MoSi2 displays more mass gain in water vapor than in air. The oxidation kinetics observed in water vapor differ from that of the air samples. Two volatile oxides, MoO2 (OH)2 and Si(OH)4, are thought to be the species responsible for the varied kinetics, at 670–877 K and at 1498 K, respectively. Increased oxidation (140–300 mg/cm 2 ) was observed from 980–1084 K in water vapor, where passivation is observed in air.